How I treat patients who are refractory to platelet transfusions - Nahirniak, Susan; Nadarajan, Veera; Stanworth, Simon J (Blood, 2025)
Patients with thrombocytopenia requiring ongoing platelet transfusion support may develop inadequate platelet count increments, referred to as platelet refractoriness (PR), which further complicates their care. The underlying etiologies of PR can be broadly divided into immune and nonimmune causes. A high index of suspicion is required to initiate testing for alloimmunization, and the leading culprit in immune PR is the development of class I HLA antibodies. The approach to diagnosis of immune PR has changed over recent years with new technologies, but questions regarding the clinical significance and interpretation of these methods have not been conclusively answered. The provision of HLA-matched platelets requires close and timely coordination between transfusion services and clinical teams; however, the true impact of their provision on clinical outcomes is not clear. This paper reviews diagnostic and management challenges, appraises the existing data available to support treatment options, and identifies research gaps.